Information skills and library knowledge for higher education teachers - Sanches, Tatiana (2020)
The explosion of information, not only in print, but in a digital context has become a fertile area for exploring, transmitting, and disseminating information, enabling learning and teaching, transforming and creating new knowledge. Higher education teachers need to be aware of how to train and guide their students in multiple ways to knowledge, including the ability to deal with information in print and digital contexts, so information literacy training should be a priority. This paper aims to list the skills to be developed by these teachers, preferably integrated into their professional development. Starting from the framework of tried-and-tested models, a flexible and comprehensive content structure is proposed, considering the need for their transfer to students. The importance of collaborative work with higher education libraries is stressed.